HUBUNGAN KAUSALITAS ZAKAT DAN PEMBIAYAAN TERHADAP PERTUMBUHAN EKONOMI - sandi mulyadi; Sri Mulyati (MUSLIMPRENEUR : Jurnal Ekonomi dan Kajian Keislaman, 2023)
This study aims to describe the causal relationship between zakat, financing and economic growth in Indonesia during this pandemic, the variables used are zakat, financing and economic growth. The research method uses quantitative methods by analyzing secondary data which is processed using Eviews 10 with the Granger causality tests method and using monthly time series data from 2011-2021. The results of the data processing show that economic growth has a one-way relationship with zakat and financing, namely economic growth has an influence on zakat and financing and financing has a one-way relationship with zakat, namely financing has an influence on zakat.